PENDEKATAN PSIKOLOGI DALAM UPAYA PERSIAPAN BIMBINGAN KARIR PADA SISWA KELAS 12 SMAN 2 MAKASSAR - Iindah Dwi Cahyani Ilyas; Ahnan Murtadho; Nur Hikmah; Fitrah Ramadhani; M Ahkam Alwi (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
Students who are in high school, especially class XII, must be able to understand themselves and know which career is suitable for them. The psychoeducation program about "Who am I" is psychoeducation designed by Psychology students at Makassar State University and Psychology students at Bosowa University with the approval of the counseling guidance (BK) teacher at SMAN 2 Makassar. The aim of this psychoeducation is to ensure that students at SMAN 2 Makassar are able to recognize and be aware of themselves to make it easier for participants to determine their next career. The method used is a psychoeducational method, which aims to provide information and training to change students' understanding through the material presented by the presenters. The results of providing psychoeducation "Who am I" show that students are better able to recognize themselves and recognize their potential.